Comparison of Portugal and Spain tourism websites - Morais, Elisabete Paulo (2019)
A generalization of the use of websites in tourism and in other areas has not always been synonymous of quality, thus justifying the search for evaluation of this type of software product, which is required systematically and effectively.Although, it is difficult to make a systematic and complete evaluation on websites, they are quality due to their diversity of functionalities, which make them complex to analyses. Many studies have proposed new website evaluation frameworks and criteria. The main objective of this paper is to analyse Portugal and Spain tourism websites, using one model for evaluate tourism websites and a qualitative method approach in order to assess the quality of the respective websites and to identify possible improvements.